2010
DOI: 10.1243/09544062jmes2296
|View full text |Cite
|
Sign up to set email alerts
|

Some important aspects of thermal elastohydrodynamic lubrication

Abstract: Thermal effect in elastohydrodynamic lubrication (EHL) has been the subject of study for the last four decades; however, some important aspects related to the physical behaviour of the lubricant in response to pressure, temperature, and shear rate remain largely neglected. This paper presents a brief review of the thermal EHL literature and sheds light on the importance of accurate characterization of the lubricant properties such as viscosity, density, rheology, and thermal conductivity. Full thermal EHL line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The unique characteristics of ILs make these materials promising candidates for use as industrial lubricants, especially under hydrodynamic and elastohydrodynamic regimes. ,, Kumar et al observed that not enough attention is paid to the importance of high-pressure lubricant properties, such as the density and thermal expansibility. Pensado et al also proved that the pressure profile of viscosity should consider the pressure–temperature path of thermal expansibilities and the isothermal compressibilities of IL lubricants to model ILs.…”
Section: Importance Of Speed Of Sound Knowledge For the Chemical Engi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The unique characteristics of ILs make these materials promising candidates for use as industrial lubricants, especially under hydrodynamic and elastohydrodynamic regimes. ,, Kumar et al observed that not enough attention is paid to the importance of high-pressure lubricant properties, such as the density and thermal expansibility. Pensado et al also proved that the pressure profile of viscosity should consider the pressure–temperature path of thermal expansibilities and the isothermal compressibilities of IL lubricants to model ILs.…”
Section: Importance Of Speed Of Sound Knowledge For the Chemical Engi...mentioning
confidence: 99%
“…The significance of this problem has also been noted by Franca et al 333 The unique characteristics of ILs make these materials promising candidates for use as industrial lubricants, especially under hydrodynamic and elastohydrodynamic regimes. 320,334,335 Kumar et al 335 observed that not enough attention is paid to the importance of high-pressure lubricant properties, such as the density and thermal expansibility. Pensado et al 336 also proved that the pressure profile of viscosity should consider the pressure−temperature path of thermal expansibilities and the isothermal compressibilities of IL lubricants to model ILs.…”
Section: Importance Of Speed Of Sound Knowledge For the Chemical Engi...mentioning
confidence: 99%
“…Beginning with the first full EHL simulation employing real pressure and shear dependent viscosity, measured in viscometers [8], there have been revolutionary advances in the understanding of friction and film-forming. See [9][10][11][12] for examples. While it is apparent that the Newtonian film thickness solution is much less widely applicable than previously thought, Newtonian inlets do exist in practical problems and, even when the viscosity is shear dependent in the inlet, it remains necessary to describe the pressure dependence of the low-shear viscosity to apply any shear-thinning solution using superposition.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Furthermore, it was found that heat generated by friction can produce a local temperature rise, leading to analysis of the thermal effects, and therefore giving rise to the so-called thermal elastohydrodynamic lubrication. 8,9 Many other studies [10][11][12] contributed to a better understanding of the main factors which influence the behaviour of the lubricant and the quantitative effects of each.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous analyses observed that under the severe operating conditions of elastohydrodynamics, the rheology of many common lubricants varies from Newtonian to pseudoplastic . Furthermore, it was found that heat generated by friction can produce a local temperature rise, leading to analysis of the thermal effects, and therefore giving rise to the so‐called thermal elastohydrodynamic lubrication . Many other studies contributed to a better understanding of the main factors which influence the behaviour of the lubricant and the quantitative effects of each.…”
Section: Introductionmentioning
confidence: 99%